Water footprint of low-tech digesters for bioenergy recovery from waste - Kurt Ziegler-Rodriguez; Irene Josa; Liliana Castro; Jaime Jaimes-Estévez; Humberto Escalante; Marianna Garfí (Environmental Impact Assessment Review, 2027)

Environmental and Economic Life Cycle Assessment of low-tech digesters coupled with gasification technology implemented in a small-scale dairy farm - Kurt Ziegler-Rodriguez; Irene Josa; Liliana Castro; Jaime Jaimes-Estévez; Isabel Daniela Ardila-Beltrán; Laura Camila Romero-Melo; Humberto Escalante; Marianna Garfí (Journal of Cleaner Production, 2026)

Multi-mechanistic mitochondria-mediated N-methylated YKWYYRGAA-decorated nano-chitosan conjugate carrier for treatment of NRAS-mutant-harbouring lung carcinoma - Yazid Zaiki; Chin Fei Chee; Lucia Ageitos; Idanawati Naharudin; Badrul Hisyam Zainudin; Lek Mun Leong; Rodriguez González Jaime; Carlos Jimenez; Chee Yuen Gan; Daniela Traini; Tin Wui Wong (Carbohydrate Polymers, 2026)

Bioactive Extracts from Yucatán Marine Invertebrates as Modulators of Microalgal Dynamics - Dawrin Pech-Puch; Rita Pires; Bárbara A. Rebelo; Diana Grilo; Carlos Gonzáles-Salas; Susana Eunice Calva-Pérez; Susana M. Gomes; Harold Villegas-Hernández; Sergio Guillén-Hernández; Abel M. Forero; Jaime Rodriguez; Carlos Jiménez; et al. (Marine Biotechnology, 2026)
The marine environment is a rich source of bioactive compounds with a wide range of applications. In this study, 65 extracts from sponges, ascidians, and a gorgonian collected from the Yucatán Peninsula, Mexico, were evaluated for their modulatory effects on the growth of four microalgal species. Some extracts were found to exhibit pronounced algicidal activity, while others promoted growth. Bioassay-guided fractionation of the extract from Haliclona (Rhizoniera) curacaoensis led to the identification of arenosclerins A and C as potent algicidal agents, active across all tested microalgae. In contrast, the extract from Halichondria melanadocia enhanced microalgal growth, and chemical analysis revealed the presence of medelamine A and B as putative growth-promoting compounds. This study provides a new report on microalgae-modulating activities of marine sponge metabolites. The dual activity observed, both inhibitory and stimulatory, not only contributes to our understanding of marine compound diversity but also underscores the potential of these marine-derived compounds for sustainable environmental management practices.

Type A Toxin Protocol for Chronic Migraine Without Aesthetic Alteration. FaceLess Injection PAradigm Study (FLIPAS) - Jaime Rodriguez-Vico (Toxicon, 2026)

Type A Toxin Protocol for Chronic Migraine Without Aesthetic Alteration. FaceLess Injection PAradigm Study (FLIPAS) - Jaime Rodriguez-Vico (Toxicon, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Phytochemicals as promising agents against pathogenic free-living amoebas - Erick P. Gutiérrez-Grijalva; Laura A. Contreras-Angulo; Marilyn Shomara Criollo-Mendoza; J. Basilio Heredia; Jaime López-Cervantes; Dalia Isabel Sánchez-Machado; Jose Reyes Gonzalez-Galaviz; Libia Zulema Rodriguez-Anaya (Phytochemistry Reviews, 2026)

Genetic diversity of Mycoplasma bovis isolated from bovine respiratory disease and bovine mastitis in Chile - Matías Goddard; Joscelyn San Martín; Jose Arturo Molina-Mora; Luis Collado; Jaime Rodriguez; Nicolás Galarce; Armin Mella (Veterinary Microbiology, 2025)

Enhancing Stability and Biocompatibility of Antitubercular Peptides LL-37 and IDR-1018 Through Liposomal Encapsulation - Jaime Huerta-Elias; Juan Trujillo-Paez; Yolanda Jacobo-Delgado; Oscar Gonzalez-Muñiz; Adrian Rodriguez-Carlos; Gabriela Navarro-Tovar; Bruno Rivas-Santiago (Journal of Pharmaceutical Innovation, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Pollen DNA metabarcoding reveals cryptic diversity and high spatial turnover in alpine plant–pollinator networks - Francisco Encinas‐Viso; Jessica Bovill; David E. Albrecht; Jaime Florez‐Fernandez; Bryan Lessard; James Lumbers; Juanita Rodriguez; Alexander Schmidt‐Lebuhn; Andreas Zwick; Liz Milla (Molecular Ecology, 2023)
Alpine plant–pollinator communities play an important role in the functioning of alpine ecosystems, which are highly threatened by climate change. However, we still have a poor understanding of how environmental factors and spatiotemporal variability shape these communities. Here, we investigate what drives structure and beta diversity in a plant–pollinator metacommunity from the Australian alpine region using two approaches: pollen DNA metabarcoding (MB) and observations. Individual pollinators often carry pollen from multiple plant species, and therefore we expected MB to reveal a more diverse and complex network structure. We used two gene regions (ITS2 and trnL ) to identify plant species present in the pollen loads of 154 insect pollinator specimens from three alpine habitats and construct MB networks, and compared them to networks based on observations alone. We compared species and interaction turnover across space for both types of networks, and evaluated their differences for plant phylogenetic diversity and beta diversity. We found significant structural differences between the two types of networks; notably, MB networks were much less specialized but more diverse than observation networks, with MB detecting many cryptic plant species. Both approaches revealed that alpine pollination networks are very generalized, but we estimated a high spatial turnover of plant species (0.79) and interaction rewiring (0.6) as well as high plant phylogenetic diversity (0.68) driven by habitat differences based on the larger diversity of plant species and species interactions detected with MB. Overall, our findings show that habitat and microclimatic heterogeneity drives diversity and fine‐scale spatial turnover of alpine plant–pollinator networks.

Geological context and human exposures to element mixtures in mining and agricultural settings in Colombia - Oscar Florez-Vargas; Eugenio Vilanova; Carolina Alcaide; José A. Henao; Carlos A. Villarreal-Jaimes; Olga M. Medina-Pérez; Laura A. Rodriguez-Villamizar; Alvaro J. Idrovo; Luz H. Sánchez-Rodríguez (Science of The Total Environment, 2023)

Embryo biopsy and vitrification applied to a commercial embryo transfer program in Argentina - Fernando L Riera; Jaime E Roldán; Maria B Rodriguez; Fernando A Jastrzebski; Monique Lopez Echeverria; Katrin Hinrichs (Journal of Equine Veterinary Science, 2023)

The impacts of social determinants of health and cardiometabolic factors on cognitive and functional aging in Colombian underserved populations - Hernando Santamaria-Garcia; Sebastian Moguilner; Odir Antonio Rodriguez-Villagra; Felipe Botero-Rodriguez; Stefanie Danielle Pina-Escudero; Gary O’Donovan; Cecilia Albala; Diana Matallana; Michael Schulte; Andrea Slachevsky; Jennifer S. Yokoyama; Katherine Possin; et al. (GeroScience, 2023)
Global initiatives call for further understanding of the impact of inequity on aging across underserved populations. Previous research in low- and middle-income countries (LMICs) presents limitations in assessing combined sources of inequity and outcomes (i.e., cognition and functionality). In this study, we assessed how social determinants of health (SDH), cardiometabolic factors (CMFs), and other medical/social factors predict cognition and functionality in an aging Colombian population. We ran a cross-sectional study that combined theory- (structural equation models) and data-driven (machine learning) approaches in a population-based study ( N = 23,694; M = 69.8 years) to assess the best predictors of cognition and functionality. We found that a combination of SDH and CMF accurately predicted cognition and functionality, although SDH was the stronger predictor. Cognition was predicted with the highest accuracy by SDH, followed by demographics, CMF, and other factors. A combination of SDH, age, CMF, and additional physical/psychological factors were the best predictors of functional status. Results highlight the role of inequity in predicting brain health and advancing solutions to reduce the cognitive and functional decline in LMICs.

Invasive trees rely more on mycorrhizas, countering the ideal‐weed hypothesis - Jaime Moyano; Mariano A. Rodriguez‐Cabal; Martin A. Nuñez (Ecology, 2021)
The ideal‐weed hypothesis predicts that invasive plants should be less dependent on mutualisms. However, evidence in favor of or against this hypothesis comes mainly from observational studies. Here, we experimentally tested this hypothesis using a two‐factor greenhouse experiment, comparing the seedling growth response of different Pinus species (varying in invasiveness) to ectomycorrhizal fungal inoculation. Most species showed no response until they were 6 mo old, at which point inoculation increased growth between 10 and 260% among the different species. This growth response was higher for species with lower seed mass, higher dispersal ability, higher Z score (a proxy for invasiveness) and higher number of naturalized regions, all of which correspond to higher invasiveness. Our results show that timing is a crucial factor when comparing mycorrhizal dependency of different species. Dependence on mutualistic microorganisms could be part of a strategy in which invasive species produce smaller seeds, in greater number, which can disperse further, but where seedlings are more reliant on mycorrhizas to improve access to water, nutrients, and protection from pathogens. Our results suggest that reliance on mutualisms may enhance, rather than limit, nonnative species in their ability to spread, establish, and colonize.

Recombinant C-Terminal Domains from Scorpine-like Peptides Inhibit the Plasmodium berghei Ookinete Development In Vitro - Leonel Vargas-Jaimes; María Carmen Rodriguez; Rocío Argotte-Ramos; Víctor Rivelino Juárez-González; Nina Pastor; Catherine Cesa-Luna; Lourival D. Possani; Verónica Quintero-Hernández (International Journal of Peptide Research and Therapeutics, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Predicting distributional shifts of commercially important seaweed species in the Subantarctic tip of South America under future environmental changes - Silvia Murcia; Pablo Riul; Fabio Mendez; Juan Pablo Rodriguez; Sebastian Rosenfeld; Jaime Ojeda; Johanna Marambio; Andrés Mansilla (Journal of Applied Phycology, 2020)

Acute administration of levetiracetam in tonic pain model modulates gene expression of 5HT1A and 5HT7 receptors in the thalamus of rats (Rattus norvergicus) - José Luis Cortes-Altamirano; Samuel Reyes-Long; Herlinda Bonilla-Jaime; Denise Clavijo-Cornejo; Javier Vargas; Cindy Bandala; Alfonso Alfaro-Rodriguez (Molecular Biology Reports, 2020)

Highly invasive tree species are more dependent on mutualisms - Jaime Moyano; Mariano A. Rodriguez‐Cabal; Martin A. Nuñez (Ecology, 2020)
Why some species become invasive while others do not remains an elusive question. It has been proposed that invasive species should depend less on mutualisms, because their spread would then be less constrained by the availability of mutualistic partners. We tested this idea with the genus Pinus , whose degree of invasiveness is known at the species level (being highly and negatively correlated with seed size), and which forms obligate mutualistic associations with ectomycorrhizal fungi (EMF). Mycorrhizal dependence is defined as the degree to which a plant needs the mycorrhizal fungi to show the maximum growth. In this regard, we use plant growth response to mycorrhizal fungi as a proxy for mycorrhizal dependence. We assessed the responsiveness of Pinus species to EMF using 1,206 contrasts published on 34 species, and matched these data with data on Pinus species invasiveness. Surprisingly, we found that species that are more invasive depend more on mutualisms (EMF). Seedling growth of species with smaller seeds benefited more from mutualisms, indicating a higher dependence. A higher reliance on EMF could be part of a strategy in which small‐seeded species produce more seeds that can disperse further, and these species are likely to establish only if facilitated by mycorrhizal fungi. On the contrary, big‐seeded species showed a lower dependence on EMF, which may be explained by their tolerance to stressful conditions during establishment. However, the limited dispersal of larger seeds may limit the spread of these species. We present strong evidence against a venerable belief in ecology that species that rely more on mutualisms are less prone to invade, and suggest that in certain circumstances greater reliance on mutualists can increase spread capacity.

Seed predation does not explain pine invasion success - Jaime Moyano; Mariana C. Chiuffo; Martín A. Nuñez; Mariano A. Rodriguez-Cabal (Oecologia, 2019)

Seed predation of non-native species along a precipitation gradient - Mariana C. Chiuffo; Jaime Moyano; Mariano A. Rodriguez-Cabal; Martín A. Nuñez (Plant Ecology, 2018)

ATLANTIC AMPHIBIANS : a data set of amphibian communities from the Atlantic Forests of South America - Maurício Humberto Vancine; Kauã da Silva Duarte; Yuri Silva de Souza; João Gabriel Ribeiro Giovanelli; Paulo Mateus Martins‐Sobrinho; Ariel López; Rafael Parelli Bovo; Fábio Maffei; Marília Bruzzi Lion; José Wagner Ribeiro Júnior; Ricardo Brassaloti; Carolina Ortiz Rocha da Costa; et al. (Ecology, 2018)
Amphibians are among the most threatened vertebrates in the world and this is also true for those inhabiting the Atlantic Forest hotspot, living in ecosystems that are highly degraded and threatened by anthropogenic activities. We present a data set containing information about amphibian communities sampled throughout the Atlantic Forest Biome in South America. The data were extracted from 389 bibliographic references (articles, books, theses, and dissertations) representing inventories of amphibian communities from 1940 to 2017. The data set includes 17,619 records of 528 species with taxonomic certainty, from 1,163 study sites. Of all the records, 14,450 (82%) were classified using the criterion of endemism; of those, 7,787 (44%) were considered endemic and 6,663 (38%) were not. Historically, multiple sampling methods were used to survey amphibians, the most representative methods being active surveys (82.1%), surveys at breeding sites (20%), pitfall traps (15.3%), and occasional encounters (14.5%). Species richness averaged 15.2 ± 11.3 (mean ± SD) , ranging from 1 to 80 species per site. We found a low dominance in the communities, with 10 species occurring in about 26% of communities: Physalaemus cuvieri (4.1%), Dendropsophus minutus (3.8%), Boana faber (3.1%), Scinax fuscovarius (2.8%), Leptodactylus latrans (2.7%), Leptodactylus fuscus (2.6%), Boana albopunctata (2.3%), Dendropsophus nanus (1.6%), Rhinella ornata (1.6%), and Leptodactylus mystacinus (1.6%). This data set represents a major effort to compile inventories of amphibian communities for the Neotropical region, filling a large gap in the data on the Atlantic Forest hotspot. We hope this data set can be used as a credible tool in the proposal of new studies on amphibian sampling and even in the development of conservation planning for these taxa. This information also has great relevance for macroecological studies, being foundational for both conservation and restoration strategies in this biodiversity hotspot. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching events.

Still no evidence that pathogen accumulation can revert the impact of invasive plant species - Mariana C. Chiuffo; Nahuel Policelli; Jaime Moyano; Agostina Torres; Mariano A. Rodriguez-Cabal; Martín A. Nuñez (Biological Invasions, 2018)

Pathogen accumulation cannot undo the impact of invasive species - Nahuel Policelli; Mariana C. Chiuffo; Jaime Moyano; Agostina Torres; Mariano A. Rodriguez-Cabal; Martín A. Nuñez (Biological Invasions, 2018)

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Financial Risk Assessment and Optimal Planning of Biofuels Supply Chains under Uncertainty - José Ezequiel Santibañez-Aguilar; Gonzalo Guillen-Gosálbez; Ricardo Morales-Rodriguez; Laureano Jiménez-Esteller; Agustín Jaime Castro-Montoya; José María Ponce-Ortega (BioEnergy Research, 2016)

Quetiapine extended-release (Seroquel-XR) versus amitriptyline monotherapy for treating patients with fibromyalgia: a 16-week, randomized, flexible-dose, open-label trial - Elena P. Calandre; Fernando Rico-Villademoros; Jaime Galán; Rocio Molina-Barea; Juan S. Vilchez; Carmen M. Rodriguez-Lopez; Javier Hidalgo-Tallon; Piedad Morillas-Arques (Psychopharmacology, 2014)

Growth responses to temperature, salinity and nutrient variations, and biomass variation and phenology of Ahnfeltia plicata (Rhodophyta, Ahnfeltiales): a commercially interesting agarophyte from the Magellanic Region, Chile - Andres Mansilla; Juan Pablo Rodriguez; Jonatas M. C. Souza; Sebastián Rosenfeld; Jaime Ojeda; Nair S. Yokoya (Journal of Applied Phycology, 2014)

Antiviral compounds obtained from microalgae commonly used as carotenoid sources - Susana Santoyo; Laura Jaime; Merichel Plaza; Miguel Herrero; Irene Rodriguez-Meizoso; Elena Ibañez; Guillermo Reglero (Journal of Applied Phycology, 2012)

Exploring the influence of shrubs on herbaceous communities in a Mediterranean climatic context of two spatial scales - Jaime Madrigal; Jose Antonio García-Rodriguez; Roberto Julian; Angel Puerto; Belen Fernández-Santos (Plant Ecology, 2008)

Estimation of coancestry in Iberian pigs using molecular markers - Miguel Toro; Carmen Barragán; Cristina Óvilo; Jaime Rodrigañez; Carmen Rodriguez; Luis Silió (Conservation Genetics, 2002)

Genealogical Analysis of a Closed Herd of Black Hairless Iberian Pigs - Miguel A. Toro; Jaime Rodriganez; Luis Silio; Carmen Rodriguez (Conservation Biology, 2000)

Genealogical Analysis of a Closed Herd of Black Hairless Iberian Pigs - Miguel A. Toro; Jaime Rodrigañez; Luis Silio; Carmen Rodriguez (Conservation Biology, 2000)
Livestock breeds are recognized as important components of world biodiversity. The Iberian pig is a swine breed well adapted to the Mediterranean forest ecosystem and provides cured products of high quality. The ancient population of Iberian pigs ( Sus scrofa meridionalis ) was differentiated in several local types, the black hairless pigs representing the fattest genetic type. The conservation program of the Guadyerbas strain has maintained this germplasm isolated since 1945 as a closed population in an experimental herd. The complete pedigree, with 1000 breeding animals descending from 24 founders, has been used to measure along the successive cohorts of breeding animals the effective number of founders, effective number of nonfounders, founder genome equivalents, and expected number of founders' surviving alleles. For the last cohort, the values were 10.34, 1.42, 1.25, and 4.06, respectively. The evolution of inbreeding and coancestry and its components attributable to each founder were also studied. The rate of increase in inbreeding and coancestry was 2.21% per cohort, or 0.906% per year. Finally, the effect of family structure and mating tactics on the evolution of coancestry was also analyzed. The greatest rates of coancestry per cohort were attributable to unbalanced family sizes, and the use of minimum coancestry matings effectively delayed the increase in inbreeding.